Teaching English spelling : - Shemesh, Ruth (Cambridge Univ. Press, 2000)
Teaching English Spelling, a resource book of supplementary activities for practicing common English spelling patterns, can be used with both first-language and foriegn- and second-language learners at a variety of levels. A typical chapter in Teaching English Spelling focuses on a single phoneme and is then divided into three to five easy-to-follow lesson plans, each on a different letter for the target sound.